The Influence of Organizational Culture Leadership Style and Work Stress on Commitment - Agil Panji Susilo; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Leadership Style, Organizational Culture and Work Stress on Organizational Commitment at PT. Ciomas Adisatwa Sidoarjo. This research is a type of quantitative research with hypothesis testing. The sample used in this study are employees of PT. Ciomas Adisatwa F&A, P&GA, Purchasing and Ppic divisions, totaling 39 employees. This study uses quantitative data analysis techniques. Descriptive statistical analysis and inferential statistical analysis were used to analyze quantitative data. The analytical tool used in this research is SPSS Software. The data used in this study are questionnaire data and data sourced from PT. Ciomas Adiasatwa Sidoarjo. Data collection techniques using questionnaires, interviews and observations. The results of this study prove that Hypothesis 1: Leadership Style Variable has a significant and positive effect on Organizational Commitment. Hypothesis 2: Organizational Culture Variable has a significant and positive effect on Organizational Commitment. Hypothesis 3: Work Stress Variable has a significant and negative effect on Organizational Commitment. Hypothesis 4: Leadership Style, Organizational Culture and Work Stress Together have an effect on organizational commitment.